PERAN KEPUASAN PELANGGAN MEMEDIASI KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PADA PT. AIRASIA INDONESIA - Maheswari, Anak Agung Ayu Ratna; Aksari, Ni Made Asti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.03.TAHUN 2019, 2019)
The amount of activities that requires airline services demands airline companies to provide good quality services to create satisfied and loyal consumers. The purpose of this study is to explain the effect of service quality on customer satisfaction and customer loyalty, the effect of customer satisfaction on customer loyalty, and to explain the mediating role of customer satisfaction in the effect of service quality on customer loyalty of AirAsia airline. Through purposive sampling method, this study uses a sample of 130 AirAsia customers at Ngurah Rai International Airport and Denpasar City, data was collected using questionnaire with a five-point Likert scale to measure 13 indicators, and analysed using path analysis. The result shows that service quality have a positive effect on customer satisfaction and their loyalty on AirAsia airline, customer satisfaction have a positive effect on customer loyalty on AirAsia airline, and customer satisfaction mediates the effect of service quality towards customer loyalty on AirAsia airline. We recommend for AirAsia to pay close attention to the quality of its services by controlling its flight schedule punctuality to satisfy its customers, which in turn will become loyal customers of AirAsia airline.